Can Increased Endotoxin Levels in House Dust be used as an Indicator of a Mould Problem? - Mussalo-Rauhamaa, Helena; Elg, Peter; Paloheimo, Lea; Koukila-Kähkölä, Pirkko (Global Journal of Respiratory Care, 2018)
Endotoxins are common indoor biocontaminants. Our purpose was to investigate the association of endotoxin content with mould problems in house dust in buildings, to determine whether endotoxins can be used as an indicator of the presence of moulds in buildings. The participants were selected from the Clinic for Indoor Air Health Problems on the basis of symptoms attributed to indoor air problems. We examined their health status. House dust was collected in new vacuum cleaner bags from surfaces in the rooms of their homes or workplaces. We measured the endotoxin concentrations in the house dust of 13 homes and 9 workplaces of the 19 participants, using a quantitative limulus test. The median endotoxin concentrations in the house dust of their homes was 9.9, and the range was 1.9–103 EU/mg; and in the house dust of workplaces it was 4.5, and the range 0.5–81 EU/mg. We found higher house dust endotoxin concentrations in rooms in which moisture problems had been identified or in dwellings in which pets were kept. Our pilot study suggests that endotoxins may be a useful additional tool for estimating possible mould contamination at homes or workplaces.